Synthesis of CF3-Containing 1,2,3,4-Tetrahydroisoquinoline-3-Phosphonates via Regioselective Ruthenium-Catalyzed Co-cyclotrimerization of 1,7-Azadiynes - Zotova, Maria A.; Vorobyeva, Daria V.; Dixneuf, Pierre H.; Bruneau, Christian; Osipov, Sergey N. (Synlett, 2013)
An efficient access to novel trifluoromethyl-substituted phosphonate analogues of 1,2,3,4-tetrahydroisoquinoline-3-carboxylic acid (TIC) derivatives based on regioselective ruthenium-catalyzed co-cyclotrimerization of functionalized 1,7-diynes with various alkynes has been developed using RuClCp*cod and preferably Grubbs second-generation catalysts.
Keywords: α-aminophosphonates; 1,7-azadiynes; alkynes; cyclotrimerization; ruthenium catalysis